Method for manufacturing cation exchange resin and method for purifying organic acid solution
Patent Information
- Application Number
- KR1020257014148
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-06
- Filing Date
- 2023-08-17
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-08-17
Smart Images

Figure 112025048238062-PCT00001 
Figure 112025048238062-PCT00002 
Figure 112025048238062-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a cation exchange resin and a method for advanced purification of an organic acid solution using said cation exchange resin. Background Technology
[0002] In semiconductor manufacturing processes, various high-purity chemicals are used, and there is a strong demand for reducing metal impurities in these chemicals, not limited to ultrapure water. Ion exchange resins (cation exchange resins, anion exchange resins, chelate resins) are used to remove metal impurities in these chemicals. Therefore, there is a demand for reducing eluent from the ion exchange resins themselves that are used to purify these chemicals.
[0003] As a method for reducing the metal impurity content of an ion exchange resin, a method of contacting the ion exchange resin with a high-purity inorganic acid solution having a metal impurity content of 1 mg / L or less has been proposed (Patent Document 1). In addition, a method of purifying the ion exchange resin using an aqueous inorganic acid solution containing a chelating agent such as ethylenediamine tetraacetic acid has been proposed (Patent Document 2). Prior art literature
[0004] (Patent Document 0001) JP 2007-117781 A (Patent Document 0002) JP 2010-234339 A The problem to be solved
[0005] In particular, when purifying organic acid solutions using ion exchange resins, there is a tendency for the amount of metal leaching from the ion exchange resin to increase due to the metal dissolution or extraction effects of the organic acid solution itself, which is the target of purification (the solution to be treated). Consequently, there have been cases where trace amounts of metal leaching became a problem even when organic acid solutions were purified using ion exchange resins purified by the method described in the aforementioned patent document. Furthermore, in the purification of organic acid solutions, there was a problem of increased costs due to the short lifespan of the ion exchange resins used and the high frequency of resin replacement.
[0006] Accordingly, the present invention aims to provide a method for manufacturing a cation exchange resin that reduces the metal impurity content in the cation exchange resin and exhibits minimal metal leaching even when used for the purification of organic acid solutions. Furthermore, the present invention aims to provide a method for the advanced purification of organic acid solutions using the above-described cation exchange resin capable of regenerative operation. means of solving the problem
[0007] The present invention is a method for manufacturing a cation exchange resin comprising: a first regeneration process for obtaining a cation exchange resin (B) by contacting a cation exchange resin (A) with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more; a purification process for purifying an organic acid solution by contacting the cation exchange resin (B) with an organic acid solution having a metal impurity amount of 2 mg / L or less and a concentration of 3 mass% or more; and a second regeneration process for obtaining a cation exchange resin (C) by contacting the cation exchange resin (B) after the purification process with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more.
[0008] In addition, the present invention is a method for purifying an organic acid solution comprising a first regeneration process of obtaining a cation exchange resin (B) by contacting a cation exchange resin (A) with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more, and a purification process of purifying the organic acid solution by contacting the cation exchange resin (B) with an organic acid solution having a metal impurity amount of 2 mg / L or less and a concentration of 3 mass% or more, wherein the cation exchange resin (B) after the purification process is reused as the cation exchange resin (A) used in the first regeneration process, and the first regeneration process and the purification process are repeated one or more times. Effects of the invention
[0009] According to the present invention, the metal impurity content in the cation exchange resin is reduced, and a cation exchange resin with low metal leaching can be obtained even when used for the purification of organic acid solutions. Furthermore, by using the said cation exchange resin, the metal impurities contained in the organic acid solution can be stably reduced. In addition, according to the present invention, a method for the advanced purification of an organic acid solution can be provided, which suppresses cost increases by regenerating and operating the said cation exchange resin. Specific details for implementing the invention
[0010] Method for manufacturing cation exchange resin
[0011] A method for manufacturing a cation exchange resin with reduced metal leaching amount according to the present invention comprises the following steps: a first regeneration step of obtaining a cation exchange resin (B) by contacting a cation exchange resin (A) with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more; a purification step of purifying an organic acid solution by contacting the cation exchange resin (B) with an organic acid solution having a metal impurity amount of 2 mg / L or less and a concentration of 3 mass% or more; and a second regeneration step of obtaining a cation exchange resin (C) by contacting the cation exchange resin (B) after the purification step with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more. Each step is described in detail below.
[0012] [1st Regeneration Process]
[0013] In the first regeneration process, an H-type (hydrogen ion type) cation exchange resin (B) is obtained by contacting an inorganic acid solution, which has a metal impurity content of 1 mg / L or less and a concentration of 5 mass% or more, with a cation exchange resin (A) as a regenerating agent. Here, "cation exchange resin (A)" refers to the cation exchange resin before purification, that is, before regeneration, and "cation exchange resin (B)" refers to the cation exchange resin after purification, that is, after regeneration. This process is a process for reducing the metal impurity content of the cation exchange resin used for purification prior to the purification of the organic acid solution.
[0014] (Cation exchange resin (A))
[0015] As for the cation exchange resin (A), salt-type cation exchange resins such as Na-type and K-type, or H-type cation exchange resins, can all be used. However, from the perspective of suppressing the increase in costs caused by the increased requirement of regenerator, it is preferable to use an H-type cation exchange resin as the cation exchange resin (A). Although the cation exchange resin (A) is not particularly limited, an organic polymer-based cation exchange resin with an organic polymer as the matrix is preferred. Examples of organic polymers serving as the matrix include styrene-based resins and acrylic-based resins.
[0016] In addition, in this specification, "styrene-based resin" means a resin comprising 50 mass% or more of a constituent unit derived from styrene or a styrene derivative, either alone or copolymerized with styrene or a styrene derivative. Examples of styrene derivatives include α-methylstyrene, vinyltoluene, chlorostyrene, ethyl styrene, i-propylstyrene, dimethyl styrene, bromostyrene, etc. As long as the styrene-based resin is composed mainly of styrene or a styrene derivative alone or copolymerized, it may also be a copolymerized with other copolymerizable vinyl monomers. Examples of such vinyl monomers include, for instance, divinylbenzene such as o-divinylbenzene, m-divinylbenzene, p-divinylbenzene; and polyfunctional monomers such as alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate and polyethylene glycol di(meth)acrylate. One or more selected from (meth)acrylonitrile, methyl (meth)acrylate, etc. Among these, divinylbenzene, ethylene glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate having an ethylene polymerization number of 4 to 16 are preferred, divinylbenzene and ethylene glycol di(meth)acrylate are more preferred, and divinylbenzene is particularly preferred.
[0017] In addition, in this specification, "acrylic resin" means a resin comprising 50 mass% or more of a constituent unit derived from acrylic acid, a constituent unit derived from methacrylic acid, a constituent unit derived from acrylic acid ester, and a constituent unit derived from methacrylic acid ester, which is homopolymerized or copolymerized with one or more selected from acrylic acid, methacrylic acid, acrylic acid ester, and methacrylic acid ester. As acrylic resins, there are homopolymers of acrylic acid, homopolymers of methacrylic acid, homopolymers of acrylic acid esters, homopolymers of methacrylic acid esters, copolymers of acrylic acid with other monomers (e.g., acrylic acid esters, methacrylic acid, methacrylic acid esters, α-olefins (e.g., ethylene, divinylbenzene, etc.)), copolymers of methacrylic acid with other monomers (e.g., acrylic acid, acrylic acid esters, methacrylic acid esters, α-olefins (e.g., ethylene, divinylbenzene, etc.)), copolymers of acrylic acid esters with other monomers (e.g., acrylic acid, methacrylic acid esters, α-olefins (e.g., ethylene, divinylbenzene, etc.)), copolymers of methacrylic acid esters with other monomers (e.g., acrylic acid, acrylic acid esters, methacrylic acid, One or more selected from copolymers with α-olefins (e.g., ethylene, divinylbenzene, etc.)) may be used. Among these, a methacrylic acid-divinylbenzene copolymer or an acrylic acid-divinylbenzene copolymer is preferred.
[0018] As for the acrylic acid ester, an alkyl ester of acrylic acid is preferred, a straight-chain alkyl ester or a branched alkyl ester of acrylic acid is more preferred, and a straight-chain alkyl ester of acrylic acid is even more preferred. In addition, the number of carbon atoms in the alkyl group included in the alkyl ester portion is preferably 1 to 4, and it is particularly preferred that the acrylic acid ester is methyl acrylate or ethyl acrylate.
[0019] As for the methacrylic acid ester, an alkyl methacrylate ester is preferred, a straight-chain alkyl ester or a branched alkyl ester of methacrylic acid is more preferred, and a straight-chain alkyl ester of methacrylic acid is even more preferred. In addition, the number of carbon atoms in the alkyl group included in the alkyl ester portion is preferably 1 to 4, and it is particularly preferred that the alkyl methacrylate ester is methyl methacrylate or ethyl methacrylate.
[0020] In addition, the matrix of the cation exchange resin (A) may be any of the following: a transparent gel type with small pore diameters, a macroreticular type (MR type) or a macroporous type (also called porous type or hypoporous type) with large pore diameters.
[0021] Examples of cation exchange resins (A) include strong acid cation exchange resins having sulfonic acid groups and weak acid cation exchange resins having carboxylic acid groups. As cation exchange resin (A), all general resins for pure water production (e.g., Amberlite series (trademark, DuPont product)) can be used. Specifically, as cation exchange resins (A), Amberlite (registered trademark) IRN99H (gel-type strong acid cation exchange resin), IR120B, IR124, 200CT (all trademarks, DuPont product); AMBERJET (registered trademark) 1060H (gel-type strong acid cation exchange resin), 1020, 1024, 1220 (all trademarks, ORGANO CORPORATION product); ORLITE (registered trademark) DS-1 (gel-type strong acid cation exchange resin), DS-4 (macroporous-type strong acid cation exchange resin) (all trade names, products of ORGANO CORPORATION); Diaion (registered trademark) SK104H, SK1B, SK110, SK112, PK208, PK212L, PK216, PK218, PK220, PK228, UBK08, UBK10, UBK12 (all trade names, products of Mitsubishi Chemical Corporation); C100, C100E, C120E, C100x10, C100x12, C150, C160, SGC650 (all trade names, products of Purolite Corp.); Examples include MonoPlus S108H, SP112, S1668 (all trade names, products of Lewatit), but are not limited to these. The cation exchange resin (A) may be used as a single type or in combination of two or more types.
[0022] In addition, a commercially available cation exchange resin purified by such a method may be used as the purified H-type cation exchange resin (B), which is obtained by contacting the cation exchange resin (A) with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more. Specifically, among the cation exchange resins exemplified above, the ORLITE series (product name: ORGANO CORPORATION) can be used as is as the cation exchange resin (B) in the purification process, which is the next process. That is, if such a cation exchange resin is used, the first regeneration process can be omitted. From the perspective of metal removal performance, it is preferable that the cation exchange resin be a strong acidic cation exchange resin, and it is more preferable that it be a strong acidic cation exchange resin with a total exchange capacity of 1.9 eq / LR or more.
[0023] The average particle diameter of the cation exchange resin is not particularly limited, but may be, for example, 0.1 mm to 1.0 mm. Here, in this specification, the average particle diameter refers to the harmonic mean diameter.
[0024] In this process, as described in Patent Document 1, metal impurities contained in the cation exchange resin (A) are removed and reduced by contacting the cation exchange resin (A) with an inorganic acid solution having a metal impurity content of 1 mg / L or less and a concentration of 5 mass% or more, thereby obtaining a purified H-type cation exchange resin (B). By contacting the cation exchange resin (A) with an inorganic acid solution having an extremely low metal impurity content, the amount of metal impurities contained in the cation exchange resin (A) can be reduced reliably and effectively, and a cation exchange resin (B) with a low amount of eluted metal impurities can be obtained. Furthermore, after contacting the cation exchange resin (A) with the inorganic acid solution, it is preferable to wash and remove the inorganic acid solution remaining in the resin using pure or ultrapure water.
[0025] The metal impurity content in the inorganic acid solution used as a regenerating agent is 1 mg / L or less, preferably 0.5 mg / L or less, and more preferably 0.2 mg / L or less. In addition, the concentration of the inorganic acid solution is 5 mass% or more. If the concentration of the inorganic acid solution is less than 5 mass%, a sufficient effect of reducing metal impurities in the cation exchange resin cannot be obtained. Although the upper limit of the concentration of the inorganic acid solution is not limited, it is typically 30 mass% or less. In addition, the concept of metal impurities contained in the inorganic acid solution includes metal impurity ions, and representative examples include sodium (Na), magnesium (Mg), calcium (Ca), and iron (Fe). As for the inorganic acid solution, an aqueous solution is preferred, and examples include hydrochloric acid, sulfuric acid, and nitric acid. "Contacting an inorganic acid solution with a cation exchange resin (A)" includes, in addition to passing an inorganic acid solution through the cation exchange resin (A), immersing the cation exchange resin (A) in an inorganic acid solution.
[0026] The total amount of metal impurities eluted when hydrochloric acid with a concentration of 3 mass% is passed through the cation exchange resin (B) obtained in the first regeneration process at a volume ratio of 25 times is preferably 5 mg / LR or less, more preferably 3 mg / LR or less. In addition, for the purpose of increasing analytical precision, the amount of metal impurities contained in the hydrochloric acid with a concentration of 3 mass% is preferably 1 mg / L or less, more preferably 0.5 mg / L or less, and more preferably 0.2 mg / L or less, but is not limited thereto. Also, "25 times the volume" of hydrochloric acid means passing a volume of hydrochloric acid 25 times the volume of the cation exchange resin (B) through it. Also, the unit " / LR" means "per 1 L volume of the cation exchange resin in a wet water state." Also, a wet water state refers to a state in which the ion exchanger is immersed in water. The volume of the ion exchanger in a wet water state can be measured using a measuring instrument such as a graduated cylinder. Here, the cation exchange resin in a wet water state can be obtained by contacting the cation exchange resin with an atmosphere of 100% relative humidity at 25°C for at least 15 minutes.
[0027] It is preferable that the content of sodium (Na), magnesium (Mg), calcium (Ca), and iron (Fe) in the inorganic acid solution having a concentration of 5 mass% or more, used as a regenerating agent, be 200 μg / L or less for each. By contacting the inorganic acid solution with a low content of these metal impurities with the cation exchange resin, the content of Na, Mg, Ca, and Fe in the cation exchange resin can be reduced reliably and effectively. Similarly, it is preferable that the content of sodium (Na), magnesium (Mg), calcium (Ca), and iron (Fe) in the hydrochloric acid having a concentration of 3% be 200 μg / L or less for each.
[0028] Known methods may be used to contact an inorganic acid solution with a cation exchange resin (A). For example, a method of passing the inorganic acid solution through a resin-filled vessel such as a column, a liquid delivery section, and a storage tank may be used. Here, the liquid delivery section includes a pump used to pass the inorganic acid solution, or a device that extrudes compressed air or nitrogen, etc. The storage tank is a vessel for collecting the inorganic acid solution or the inorganic acid solution after treatment. From a safety perspective, the temperature of the inorganic acid solution during passage may be, for example, 15°C or higher and 60°C or lower. In addition, the SV (space velocity) of the inorganic acid solution passing through the resin-filled vessel is not particularly limited, but it is preferable that it be low within the operable range. The SV of the inorganic acid solution may be, for example, 0.5 or higher and 20 or lower, preferably 10 or lower, and more preferably 5 or lower. In addition, it is preferable that the SV of the inorganic acid solution be lower than the SV of the organic acid solution in the purification process described later. It is preferable that the flow rate of the inorganic acid solution passing through relative to the amount of resin be 1 BV or higher and 40 BV or lower. Furthermore, the above-mentioned passing conditions are examples, and each condition can be adjusted appropriately. In addition, the greater the amount of high-purity inorganic acid solution used in regeneration, the more the metal impurity content of the resin can be reduced.
[0029] [Refining Process]
[0030] In the purification process, the organic acid solution is purified by contacting the cation exchange resin (B) obtained in the first regeneration process with an organic acid solution having a metal impurity amount of 2 mg / L or less and a concentration of 3 mass% or more.
[0031] (Organic acid solution)
[0032] The organic acid solution to be purified is not particularly limited as long as it is an organic acid used in the semiconductor manufacturing process. Examples of such organic acids include water-soluble organic compounds having a carboxyl group, such as formic acid, citric acid, oxalic acid, malonic acid, tartaric acid, lactic acid, and malic acid, as well as phosphonic acids, but are not limited to these. As for phosphonic acids, there is no particular limitation as long as they are organic compounds having a phosphonic acid group (-P=O(OH)2). Among these, citric acid and oxalic acid are preferred as organic acid solutions.
[0033] In the present invention, an organic acid solution having a metal impurity content of 2 mg / L or less and a concentration of 3 mass% or more is used. Typically, an organic acid solution with an organic acid concentration of 3 mass% to 60 mass% may be used. Furthermore, the total amount of metal impurities Na (sodium), Mg (magnesium), Ca (calcium), and Fe (iron) in the organic acid solution before reducing the metal impurity content (the organic acid solution before purification provided to the purification process) is preferably 2 mg / L or less, and more preferably 1 mg / L or less. Alternatively, an organic acid solution purified by a known method may be used so that the total amount of metal impurities in the organic acid solution before purification provided to the purification process falls within the above range. In addition to the above, the organic acid solution may contain K (potassium), Al (aluminum), Ni (nickel), Cr (chromium), As (arsenic), and any other metal impurities.
[0034] As a method for contacting an organic acid solution with a cation exchange resin (B), known methods may be used, for example, methods similar to those for contacting an inorganic acid solution with the cation exchange resin (A). Specifically, purification of the organic acid solution can be performed by passing the organic acid solution through a column packed with cation exchange resin (B) (column type). Alternatively, the organic acid solution may be contacted with the cation exchange resin (B) by a batch method. The temperature of the organic acid solution during passage can be, for example, 15°C or higher and 80°C or lower, taking into account that when a solid organic acid is dissolved in an aqueous solution, the organic acid is prone to precipitating at low temperatures, or the heat resistance temperature of the cation exchange resin. Furthermore, the SV (space velocity) of the organic acid solution passing through the resin-packed container is not particularly limited, but it is preferably 1 or higher and 20 or lower. The flow rate of the organic acid solution passing through relative to the amount of resin is preferably 10 BV or higher. In addition, it is desirable to set the upper limit of the flow rate by appropriately evaluating in advance the flow rate that satisfies the target. Furthermore, the above flow conditions are examples, and each condition can be adjusted appropriately. By performing the above purification process, the amount of each metal impurity in the organic acid solution can be significantly reduced to, preferably, 10 μg / L or less, and more preferably, 5 μg / L or less.
[0035] [2nd Regeneration Process]
[0036] In the second regeneration process, the cation exchange resin (B) used for purifying the organic acid solution in the purification process is again brought into contact with an inorganic acid solution having a metal impurity content of 1 mg / L or less and a concentration of 5 mass% or more. By doing so, a cation exchange resin (C) that has been regenerated from the cation exchange resin (B) is obtained. The second regeneration process is the same process as the first regeneration process, except that the "cation exchange resin (B)" used for purifying the organic acid solution—that is, the "cation exchange resin (B)" after contact with the organic acid solution—is used as the "cation exchange resin (A)" in the first regeneration process. Furthermore, as shown in the examples, it was clear that in the second regeneration process, when an inorganic acid solution with a concentration of 5 mass% or more and a metal impurity content exceeding 1 mg / L is used, the concentration of calcium (Ca) in the resin increases. For this reason, it is important to use an inorganic acid solution with a metal impurity content of 1 mg / L or less and a concentration of 5 mass% or more as a regenerating agent in the first and second regenerating processes.
[0037] The cation exchange resin (C) is obtained by undergoing a first contact with an inorganic acid aqueous solution, contact with an organic acid solution, and a second contact with an inorganic acid aqueous solution. Here, the contact between the cation exchange resin and the organic acid solution is a purification process of the organic acid solution in which metal impurities contained in the organic acid solution are removed by the cation exchange resin. On the other hand, if explained from the perspective of the cation exchange resin, this can also be described as a purification process of the cation exchange resin in which impurities that cannot be completely removed by purification (regeneration) by an inorganic acid aqueous solution are removed by the organic acid solution. That is, according to the method of the present invention, while purifying the organic acid solution to be treated, impurities contained in the cation exchange resin used for purification that cannot be completely removed by the inorganic acid aqueous solution can be removed from the cation exchange resin by contact with the organic acid solution to be treated. Furthermore, the amount of impurities contained in the cation exchange resin that cannot be completely removed by the aqueous solution of inorganic acid is trace (e.g., at a level of a few μg / L or less), and it is believed that even if such minute impurities are eluted into the organic acid solution, they do not affect the high-level purification of the organic acid solution.
[0038] When hydrochloric acid with a concentration of 3 mass% is passed through the cation exchange resin (C) obtained in the second regeneration process at a volume ratio of 25 times, the total amount of metal impurities leached out is preferably 5 mg / LR or less, more preferably 3 mg / LR or less, as with the cation exchange resin (B) obtained in the first regeneration process. In addition, various metals such as sodium (Na), magnesium (Mg), calcium (Ca), iron (Fe), and aluminum (Al) can be cited as metal impurities contained in the cation exchange resin. In particular, according to the method of the present invention, the iron content in the cation exchange resin (C) can be made smaller than the iron content in the cation exchange resin (B) obtained after the first regeneration process. Specifically, it was found that the iron content in the cation exchange resin (C) can be reduced to, for example, 70 mass% or less, preferably 50 mass% or less, by comparing it with the iron content in the cation exchange resin (B) obtained after the first regeneration process. It is known that iron forms a complex with an inorganic acid solution such as hydrochloric acid, and the said complex is adsorbed in the cation exchange resin. However, it is presumed that by contacting it with an organic acid solution, the iron that has formed a complex and is adsorbed in the cation exchange resin can be removed from the cation exchange resin by the chelating action of the organic acid. Furthermore, the above-mentioned effect of reducing the iron content can also be obtained when the purification process and the second regeneration process are repeated.
[0039] In addition, the metal impurity content of the cation exchange resin (C) can be further reduced by increasing the amount of regenerating agent (inorganic acid solution) used in the second regenerating process, not limited to iron. Specifically, the amount of inorganic acid solution used in the regeneration treatment of the resin after contact with an organic acid solution (second regenerating process) following the first contact between the cation exchange resin and the inorganic acid solution (first regenerating process) can be set to 1.0 to 3.0 times the amount used in the first regenerating process. Alternatively, when the purification process and the second regenerating process are repeated, the inorganic acid solution is passed through the cation exchange resin after the first contact with the organic acid solution, and the metal concentration, such as Ca or Fe, in the inorganic acid solution after contact with the cation exchange resin is analyzed, and the amount at which the obtained metal concentration is reduced to below a certain level is determined as the required amount of regenerating agent. In addition, in the regeneration process following the second contact with the organic acid solution, the regeneration treatment is performed using a regeneration agent in the range of 1.0 to 3.0 times the required amount of the regeneration agent specified above. Furthermore, if the metal removal performance does not meet the target value, an operation to increase the amount of the regeneration agent or an operation to increase the concentration of the regeneration agent may be added, for example, at a rate of once every few times.
[0040] [Regeneration of Cation Exchange Resin]
[0041] It is known that compared to the purification of solutions near neutrality, the lifespan of the ion exchange resin is short in the purification of organic acid solutions (see reference examples described below). That is, in the purification of organic acid solutions, the frequency of ion exchange resin replacement increases, leading to increased costs. Therefore, in order to reduce the actual frequency of ion exchange resin replacement, it is preferable to perform regeneration of the cation exchange resin in the method according to the present invention.
[0042] That is, in the method according to the present invention, the cation exchange resin (C) obtained in the second regeneration process is reused as the cation exchange resin (B) used in the purification process, and the purification process and the second regeneration process can be repeated one or more times. Thus, according to the present invention, the cation exchange resin (B) after the purification process, which was used for purifying an organic acid solution, can be regenerated and used repeatedly for purifying an organic acid solution, thereby allowing the actual frequency of ion exchange resin exchange to be reduced. In other words, it becomes possible to suppress the cost of purifying an organic acid solution.
[0043] In addition, in the present specification, "cation exchange resin (B) after purification process" means including both the cation exchange resin (B) after undergoing a purification process once and the cation exchange resin (C) obtained by regenerating the cation exchange resin (B) after undergoing a purification process once, which is then reused in the purification process, and the cation exchange resin (B) obtained after undergoing a purification process multiple times. Likewise, "cation exchange resin (C) obtained in the second regeneration process" means including both the cation exchange resin (C) after undergoing a second regeneration process once and the cation exchange resin (C) after undergoing a second regeneration process multiple times.
[0044] When the cation exchange resin (C) obtained after the second regeneration process is reused as a cation exchange resin (B) in the purification process, the purification process and the second regeneration process may be repeated one or more times, for example, five or more times, ten or more times, fifty or more times, and 100 or more times. However, when regenerating and using a cation exchange resin applied to high-level purification, such as the present invention where the metal concentration in the organic acid solution after purification is at the μg / L level, it is necessary to manage the metal impurity content of the regenerating agent or the resin after regeneration, and, if necessary, replace the deteriorated resin. In particular, organic acids are prone to causing swelling and shrinkage of the ion exchange resin. Therefore, it is important to periodically manage the deterioration status of the resin matrix.
[0045] Therefore, in particular, when the cation exchange resin (C) obtained after the second regeneration process (which is performed repeatedly) is reused as the cation exchange resin (B) in the purification process, it is desirable to measure the parameters of the cation exchange resin (C) at predetermined intervals and to replace part or all of the cation exchange resin (C) that deviates from the predetermined range for each parameter with an H-type cation exchange resin (equivalent to a newly regenerated cation exchange resin (B) that is not a reused product) obtained by contacting an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more.
[0046] Here, as a predetermined parameter, one or more selected from the group consisting of the metal impurity content of the cation exchange resin, the crack condition and non-sphericity of the surface of the cation exchange resin observed by microscopic observation, and the exchange capacity of the cation exchange resin may be cited. Among these, since it is possible to determine the deterioration state of the resin at an early stage, it is desirable to manage the deterioration state of the resin by measuring one or more selected from the group consisting of the metal impurity content of the cation exchange resin and the crack condition and non-sphericity of the surface of the cation exchange resin observed by microscopic observation at predetermined intervals.
[0047] (Metal impurity content)
[0048] When a cation exchange resin is regenerated and used repeatedly for the purification of organic acid solutions, it is believed that impurities remaining slightly during regeneration accumulate little by little within the resin. Therefore, it is desirable to periodically measure the metal impurity content in the resin and, if the metal impurity content exceeds a certain amount, to replace part or all of it with a new cation exchange resin. The metal impurity content can be measured, for example, by a method of eluting the metal contained in the resin using hydrochloric acid (hydrochloric acid elution method). Specifically, the total amount of metal impurities leached out when hydrochloric acid with a concentration of 3 mass% is passed through the cation exchange resin (C) after regeneration at a volume ratio of 25 times is measured using ICP-MS. In addition, if there is a metal in the resin that cannot be eluted by acid, a microwave method (MW method) may be used to decompose the resin itself and measure the metal content. In addition to analyzing the metal impurity content, the pore distribution, volume, water retention capacity, reaction rate, and the exchange capacity described below of the ion exchange resin may also be analyzed.
[0049] It is preferable that the metal impurity content of the cation exchange resin (C) after regeneration be low, but the specific exchange target is, for example, when the metal impurity content exceeds 5 mg / LR, more preferably when it exceeds 3 mg / LR. In addition, regarding the predetermined range that serves as the exchange target, it is preferable to appropriately set it after evaluating the relationship between the metal impurity content in the organic acid solution and the metal impurity content in the resin in advance.
[0050] (Crack condition on resin surface, non-sphericity)
[0051] When purifying organic acid solutions with a concentration of 3 to 60 mass% used in semiconductor manufacturing processes, the purification process involves a liquid having a density and viscosity higher than that of water. In the purification of such organic acid solutions, pressure tends to rise when the solution is passed through the resin, and pressure tends to rise further as swelling, shrinkage, or fracture of the resin occurs. Therefore, attention must be paid not only to changes in metal removal performance but also to the influence on operating conditions, particularly regarding pressure changes during passage. As a method for measuring the crack condition on the surface of a cation exchange resin by microscopic observation, the Perfect Beads Content (PBC) method can be used to count, either visually or automatically, the percentage of resins without cracks, breakage, or fissures on the surface among a random number of cation exchange resins. In addition, as a method for measuring the non-sphericity rate by microscopic observation, a method (WBC: Whole Beads Content) can be cited, which involves counting the percentage of spherical beads among an arbitrary number of cation exchange resins using a microscope, either visually or automatically.
[0052] Regarding the cracked state (PBC) of the resin surface, the specific exchange target is the point at which the PBC of the new resin not yet used for purification becomes 70% or less, preferably 80% or less, when the PBC is set to 100%. In addition, regarding the non-sphericality rate (WBC), the specific exchange target is the point at which the non-sphericality rate becomes 80% or less, preferably 90% or less. Meanwhile, regarding the predetermined range that serves as the target for the above exchange, it is desirable to appropriately set it after evaluating the relationship between the amount of metal impurities in the organic acid solution and the PBC and WBC of the resin in advance. In the present invention, particularly when each process is repeated, it is desirable to install a particulate removal filter at the downstream end of the container for filling the resin so that particulates of the crushed ion exchange resin do not leach into the liquid to be treated.
[0053] (Exchange capacity)
[0054] If the exchange capacity decreases due to the degradation of the resin, the processing performance deteriorates. Therefore, it is desirable to replace the cation exchange resin with a new one when the exchange capacity of the cation exchange resin falls below a certain level. The exchange capacity can be measured by methods such as titration. Regarding the exchange capacity, the specific exchange target is the point at which the exchange capacity becomes 80% or less of the unused resin (new resin), preferably 90% or less. Furthermore, regarding the predetermined range serving as the exchange target, it is desirable to appropriately set it after evaluating the relationship between the amount of metal impurities in the organic acid solution and the exchange capacity of the resin in advance.
[0055] As explained above, examples of measuring each parameter of the resin include measuring the total amount of metal impurities eluted when 3 mass% hydrochloric acid is passed through the resin after regeneration at a volume ratio of 25 times using ICP-MS, or measuring the metal impurity content, exchange capacity, surface crack condition, and non-sphericity of the resin before and after regeneration (or before and after use for purification). Furthermore, by recording the obtained data as quality control data, the timing for replacing the resin can be determined based on the data before the resin deteriorates. Additionally, when replacing the deteriorated resin with a newly regenerated resin (cation exchange resin (B)) rather than a recycled product, it may be a complete or partial replacement. However, from the perspective of ease of quality control, a complete replacement is preferable.
[0056] In addition, the timing for measuring each parameter, that is, the predetermined period, is not specifically limited and can be set appropriately. For example, it may be performed every time after the purification process, every time after the second regeneration process, or whenever the purification process and the second regeneration process are repeated once, twice, or five times. Alternatively, when purifying an organic acid solution using the method according to the present invention, measurements may be performed every week, or an appropriate timing may be set to match the actual operation timing. Each parameter may be checked individually or in combination. It is possible to operate the regeneration process using an excess amount of inorganic acid without checking the parameters, but this is not desirable from the perspective of quality control.
[0057] (Storage method for resin)
[0058] In the method according to the present invention, the regenerated cation exchange resin may be used immediately for the purification of an organic acid solution, but it may also be used for the purification of an organic acid solution after being stored for a while. In addition, the cation exchange resin used for the purification of an organic acid solution may be regenerated immediately, but it may also be regenerated after being stored for a while. Furthermore, for example, if the purification of the organic acid solution and the regeneration of the cation exchange resin are carried out at different plants, it is necessary to transfer the cation exchange resin after purification.
[0059] Here, if the resin is transported in a state immersed in organic acid (the state of the cation exchange resin after purification), the following problems may occur. Organic acids have a high specific gravity, and transportation costs increase. There may be restrictions on the transportation of organic acids with a concentration in the % range. Due to agitation or vibration caused by transportation, organic acids may come into contact with liquids in places that are not normally in contact, potentially leading to metal leaching. Since the resin swells in the state immersed in organic acid, there is a possibility that the resin may suffer physical damage if stirred by vibration or the like. Furthermore, if organic acids with a concentration in the % range leak or remain in the piping, there is a risk of crystallization during drying. In particular, in semiconductor manufacturing plants, organic acids with a concentration of around 20 mass% are used; however, if the organic acid is dissolved by heating, there is a possibility that it may precipitate due to a decrease in temperature. In addition, even if the resin is in a water-immersed state after regeneration with an inorganic acid solution and subsequent cleaning with pure or ultrapure water, if the amount of water is large, the possibility of increased transportation costs is considered.
[0060] Therefore, when storing the cation exchange resin after the purification process used for the purification of an organic acid solution for purposes such as transportation, or when temporarily stopping the purification of the organic acid solution, it is desirable to replace the organic acid remaining in the cation exchange resin with water. That is, the method for manufacturing a cation exchange resin according to the present invention preferably includes a storage process between the purification process and the second regeneration process, in which the organic acid solution remaining in the cation exchange resin (B) after the purification process is replaced with water, and the water-replaced cation exchange resin (B) is stored until it is used in the second regeneration process. In addition, pure water or ultrapure water may be used as the water. Furthermore, even if the resin is in a water-immersed state as described above, since there is a possibility that transportation costs may increase if the amount of water is large, dehydration may be performed by a known method if necessary after replacement with water. In addition, the "cation exchange resin after the purification process used for purifying the organic acid solution" may be a cation exchange resin after being used once for purifying the organic acid solution (cation exchange resin (B) after the first purification process), or a cation exchange resin (B) after the purification and regeneration of the organic acid solution has been repeated multiple times.
[0061] The conditions for passing the organic acid in the cation exchange resin to be replaced with water after use in purifying the organic acid solution are not particularly limited, but, for example, an SV of 10 or less and a range of 2 BV to 30 BV is preferred. At this time, the pH of the aqueous solution at the outlet of the resin column filled with the cation exchange resin is checked, and the solution may be washed with water until it becomes weakly acidic to neutral. In addition, the concentration of the organic acid in the cation exchange resin must be diluted to a certain level and reduced to a concentration where it does not easily precipitate.
[0062] Method for Purifying Organic Acid Solutions
[0063] The method for purifying an organic acid solution according to the present invention is a method for purifying an organic acid solution using a cation exchange resin obtained by a first regeneration process or a second regeneration process in the method for manufacturing a cation exchange resin. That is, the method for purifying an organic acid solution according to the present invention comprises the following processes: a first regeneration process of obtaining a cation exchange resin (B) by contacting an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more with a cation exchange resin (A); and a purification process of purifying the organic acid solution by contacting the cation exchange resin (B) with an organic acid solution having a metal impurity amount of 2 mg / L or less and a concentration of 3 mass% or more. The method for purifying an organic acid solution according to the present invention is characterized by reusing the cation exchange resin (B) after the purification process as the cation exchange resin (A) used in the first regeneration process, and repeating the first regeneration process and the purification process one or more times. According to this method, since the cation exchange resin used for purification can be regenerated, the actual frequency of exchange of the cation exchange resin can be reduced.
[0064] The first regeneration process and the purification process in the method for purifying an organic acid solution according to the present invention are each processes corresponding to the first regeneration process and the purification process in the method for manufacturing a cation exchange resin according to the present invention described above, and a detailed description is omitted. In addition, the second and subsequent first regeneration processes, in which the cation exchange resin (B) after the purification process is reused as the cation exchange resin (A) in the first regeneration process, can be said to be a process corresponding to the second regeneration process in the method for manufacturing a cation exchange resin according to the present invention described above.
[0065] In addition, the regeneration operation of the cation exchange resin or the storage method of the resin described in the manufacturing method of the cation exchange resin according to the present invention described above can also be appropriately applied to the purification method of the organic acid solution according to the present invention.
[0066] By using the purification method according to the present invention, purification of an organic acid solution can be performed, for example, in the following flow. As a resin filling container, for example, a container of a size ranging from a water purification cartridge size (hundreds of mL) to a gas cylinder size (several L to 70 L) or a column size (50 L to 100 L) is used, and the cation exchange resin (B) obtained in the first regeneration process is filled into these containers. Subsequently, the liquid to be treated (organic acid solution) is passed through the said container to obtain a purified treated liquid (first purification process). The cation exchange resin (B) after the purification process is washed with water and dehydrated while remaining filled in the said resin filling container. Subsequently, the cation exchange resin (B) after washing with water is reused as cation exchange resin (A) to perform a regeneration treatment (second first regeneration process). Quality control of the resin after regeneration or estimation of the resin replacement time is performed based on the results of the leaching evaluation (conductivity, resistivity, TOC) from the resin after regeneration. Then, purification of the organic acid solution is performed again using the regenerated cation exchange resin (B) (provided that, if necessary, part or all of the cation exchange resin is replaced) (second purification process). Each of the above processes is repeated appropriately.
[0067] (Application of anion exchange resin)
[0068] In the above description, a method for manufacturing a cation exchange resin and a method for purifying an organic acid solution using said cation exchange resin have been described, but the present invention can also be applied in cases where an anion exchange resin is used instead of the said cation exchange resin. In an embodiment using an anion exchange resin, as the anion exchange resin after regeneration following the first regeneration process, for example, the ORLITE series (product name, ORGANO CORPORATION product) may be used, but is not limited thereto.
[0069] Examples
[0070] [Reference Example 1]: Purification of organic acid solution using high-purity purification resin
[0071] Using an H-type strong acid cation exchange resin (product name: ORLITE DS-1, manufactured by ORGANO CORPORATION) purified to high purity through the first regeneration process according to the present invention, 30 mass% citric acid (Wako Special Grade, manufactured by FUJIFILM WAKO PURE CHEMICAL CORPORATION, diluted with ultrapure water) was purified by passing it through SV5 for 6 hours (total 30 BV). The metal concentration in the citric acid before and after purification was analyzed using an Agilent 8900 triple quadrupole ICP-MS (product name: Agilent Technologies, Inc.). The results are shown in Table 1.
[0072] As shown in Table 1, the metal concentration in 30 mass% citric acid before purification was as high as about 800 μg / L, but it could be reduced to 5 μg / L or less. In other words, metal impurities could be significantly reduced from the sub-mg / L level to the single-digit μg / L level.
[0073] [Reference Examples 2 to 3]: Confirmation of the lifespan of the resin in organic acid purification
[0074] Using an H-type strong acid cation exchange resin (product name: ORLITE DS-1, product of ORGANO CORPORATION) purified to high purity through the first regeneration process according to the present invention, 30 mass% citric acid (Wako Special Grade, product of FUJIFILM WAKO PURE CHEMICAL CORPORATION, diluted with ultrapure water) was purified by passing it through SV5 for 12 hours (total 60 BV). The metal concentration in the citric acid before and after purification was analyzed in the same manner as in Reference Example 1 (Reference Example 2).
[0075] In addition, to demonstrate that the resin has a short lifespan in the purification of a strongly acidic organic acid solution, the purification of a mock solution containing metal impurities equivalent to or greater than the 30 mass% citric acid was performed using the same H-type strongly acidic cation exchange resin under the same conditions (12 hours at SV5, total 60 BV). The metal concentration in the mock solution before and after purification was analyzed in the same manner as in Reference Example 1 (Reference Example 3). In addition, the mock solution was prepared by adding a mixed standard solution for ICP-MS (product name: XSTC series, manufactured by SPEX) to pure water and diluting it with pure water.
[0076] The results of the purification tests of Reference Examples 2 and 3, along with the results of the purification test of Reference Example 1, are shown in Table 1.
[0077]
[0078] As shown in Table 1, the concentration of metal impurities in the mock solution before purification was higher than that of the 30 mass% citric acid solution before purification, but no metal elements exceeding 5 μg / L were observed at the time of passing through 60 BV (Reference Example 3). On the other hand, in the purification test of 30 mass% citric acid, 270 μg / L of Na leaked at the time of passing through 60 BV (Reference Example 2). That is, at the time of passing through 60 BV, Na in the citric acid was not adsorbed to the resin and remained in the citric acid as is. In addition, regarding As, although the concentration in the stock solution was lower than that of Na, no leakage was observed at the time of passing through 30 BV, whereas at the time of passing through 60 BV, leakage occurred up to a concentration equivalent to that of the stock solution. From these results, it was confirmed that in the purification of organic acid solutions, metal leakage occurs more rapidly compared to the purification of pure or near-neutral solutions, and the frequency of resin regeneration increases.
[0079] [Example 1]
[0080] (1st Regeneration Process)
[0081] An H-type strong acidic cation exchange resin (product name: ORLITE DS-1, ORGANO CORPORATION product, cation exchange resin (B)) was prepared by undergoing the first regeneration process according to the present invention using an inorganic acid solution having a metal impurity content of 1 mg / L or less and a concentration of 5 mass% or more. When hydrochloric acid with a concentration of 3 mass% was passed through the said cation exchange resin (B) at a volume ratio of 25 times, the total amount of metal impurities leached out was analyzed using ICP-MS (hydrochloric acid elution 1), and it was 5 mg / L or less.
[0082] (Refining process)
[0083] The cation exchange resin (B) was packed into a column (diameter: 19 mm, height: 300 mm), and a 30 mass% citric acid mock solution (metal impurity amount 2 mg / L or less, total metal impurity amount of Na, Mg, Ca and Fe 2 mg / L or less) was passed through SV5. In addition, the 30 mass% citric acid mock solution was prepared by dissolving Wako Special Grade citric acid (product of FUJIFILM WAKO PURE CHEMICAL CORPORATION) in pure water to a concentration of 30 mass%, and then adding a mixed standard solution for ICP-MS (XSTC series, product of SPEX). After that, ultrapure water was passed through SV10 for more than 2 hours, and it was confirmed that the pH of the washing water was weakly acidic (pH 4) and the citric acid concentration was sufficiently low.
[0084] (2nd Regeneration Process)
[0085] As a regeneration treatment, a second regeneration process according to the present invention was carried out by contacting the cation exchange resin (B) used in the purification process with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more (passing at a lower flow rate than the citric acid mock solution used in the purification process). When hydrochloric acid with a concentration of 3 mass% was passed through the obtained cation exchange resin (C) at a volume ratio of 25 times, the total amount of metal impurities eluted was analyzed using ICP-MS (hydrochloric acid elution 2) and was 5 mg / L or less. Then, the ratio of each metal concentration obtained from hydrochloric acid elution 1 before organic acid passage and hydrochloric acid elution 2 after organic acid passage (metal concentration after organic acid passage / metal concentration before organic acid passage) was calculated. The results are shown in Table 2.
[0086]
[0087] As shown in Table 2, compared to the cation exchange resin (B) obtained in the first regeneration process, the cation exchange resin (C) obtained after further regeneration with an inorganic acid after passing through the organic acid showed a tendency for the content of Fe to decrease significantly. It is believed that the Fe contained in the ion exchange resin was reduced by the chelating action of the organic acid at the same time as the ion exchange reaction that removes metals in the organic acid through the passage of the organic acid. From the above, it was found that by contacting the cation exchange resin with an inorganic acid, an organic acid, and an inorganic acid in this order, both the metals contained in the cation exchange resin that are difficult to remove by the inorganic acid alone and the metals that can be removed by the inorganic acid are reduced, and a highly purified cation exchange resin can be obtained.
[0088] [Example 2]
[0089] In a column (diameter: 19 mm, height: 300 mm), an H-type strong acid cation exchange resin, similar to that in Example 1, was filled as the cation exchange resin (B) that had undergone the first regeneration process (first regeneration process) according to the present invention. A 30 mass% citric acid mock solution (metal impurity amount 2 mg / L or less, total amount of metal impurities of Na, Mg, Ca, and Fe 2 mg / L or less) used in Example 1 was passed through the column (flow rate of SV3), and then, ultrapure water washing was performed as in Example 1 (first purification process). Subsequently, regarding the cation exchange resin (B) used for purification, a second regeneration process according to the present invention was carried out using an EL-grade inorganic acid solution (with a metal impurity content of 1 mg / L or less and a concentration of 5 mass% or more) (carried at a lower flow rate than the citric acid mock solution used in the purification process), and subsequently, ultrapure water washing was performed (second regeneration process). In this way, the inorganic acid regeneration (regeneration process) and the organic acid solution passing through (purification process) were repeated, and the purification of the organic acid solution was performed a total of four times. During the purification of each organic acid solution from the first to the fourth time, the metal concentration in the organic acid solution before and after purification was measured using an Agilent 8900 triple quadrupole ICP-MS (product of Agilent Technologies, Inc.), and the metal removal performance was evaluated. The metal removal performance was evaluated by calculating the metal removal rate for each metal based on the following formula. The results are shown in Table 3.
[0090] Metal removal rate (%) = {(Metal concentration before purification - Metal concentration after purification) / (Metal concentration before purification)} × 100
[0091] In addition, after the fourth purification of the organic acid solution, a regeneration treatment was performed, and the amount of metal impurities eluted (mg / LR) was analyzed when hydrochloric acid at a concentration of 3 mass% was passed through the cation exchange resin after the regeneration treatment at a volume ratio of 25. The measurement was performed using an Agilent 8900 triple quadrupole ICP-MS (product of Agilent Technologies, Inc.). The obtained amount of metal impurities was then compared with the amount of metal impurities in a new cation exchange resin (resin after the regeneration process) that was not used for the purification of the organic acid solution. For each metal, the ratio of the amount of metal impurities calculated from the amount of metal impurities in the resin after the fourth purification to the amount of metal impurities in the new resin is shown in Table 4.
[0092]
[0093]
[0094] As shown in Table 3, even when the organic acid solution was purified using a resin that had been repeatedly used for the purification of the organic acid solution, the metal removal rate from the organic acid solution exceeded 90%. In particular, for metals other than Ni, a stable metal removal rate of 99% or higher was observed even after the fourth purification. Thus, according to the present invention, it was confirmed that even a resin that has been repeatedly used for the purification of an organic acid solution can be regenerated by performing regeneration with an inorganic acid solution.
[0095] In addition, from the results in Table 4, it was observed that metals such as Ca increased during repeated use, but for Fe, a tendency to decrease was confirmed by repeating purification and regeneration. Furthermore, the total amount of metal impurities in the cation exchange resin was 5 mg / LR or less even when purification and regeneration were repeated, and it was found that it is possible to further reuse the resin to purify organic acid solutions.
[0096] [Comparative Example 1]
[0097] A cation exchange resin, after purifying a citric acid mock solution by the same method as in Example 1, was filled into a column (diameter: 19 mm, height: 300 mm). Then, a second regeneration process was carried out by passing an inorganic acid solution with a concentration of 5 mass% or more and a metal impurity content exceeding 1 mg / L through it at a flow rate lower than that of the citric acid mock solution. The amount of metal impurities in the cation exchange resin (C) obtained after regeneration was analyzed by the same method as in Example 1.
[0098] As a result, the amount of Ca contained in the cation exchange resin (C) after regeneration was more than 5 times the amount of Ca contained in the cation exchange resin (C) after the second regeneration process of Example 1.
[0099] [Example 3]
[0100] 20 mass% citric acid (Wako Special Grade, FUJIFILM WAKO PURE CHEMICAL CORPORATION product, diluted with ultrapure water, metal impurity amount 2 mg / L or less, total amount of metal impurities of Na, Mg, Ca and Fe 2 mg / L or less) was injected into a 250 mL beaker. Thereupon, a cation exchange resin (B) that had undergone the first regeneration process according to the present invention, the same as that in Example 1, was immersed and left to stand for 30 minutes (purification process). In addition, 5 BV of 20 mass% citric acid was used for the cation exchange resin (B). After settling, the citric acid was removed, and the cation exchange resin (B) after contact with the citric acid was regenerated by immersing it in an inorganic acid solution with a metal impurity content of 1 mg / L or less and a concentration of 5 mass% or more for 30 minutes (5 BV was used for the inorganic acid solution), followed by ultrapure water washing (second regeneration process). After repeating this purification process and the second regeneration process 10 more times, the PBC, WBC, and exchange capacity of the obtained resin sample were measured.
[0101] In addition, PBC was calculated by visually counting the percentage of cation exchange resins that do not have cracks, breakage, or fissures on the resin surface using a microscope (product name: Digital Microscope, KEYENCE CORPORATION product). In addition, WBC was calculated by visually counting the percentage of cation exchange resins that maintain a spherical shape using the above microscope. In addition, the exchange capacity was determined by passing acid through a cation exchange resin prepared in salt form and determining the number of moles of acid consumed by ion exchange by neutralization titration. The results are shown in Table 5. In addition, the "ultrapure water" condition in the table refers to the condition in which the above cation exchange resin (B) is immersed in an amount of ultrapure water equal to the above citric acid, and this is a condition corresponding to a new resin (that has undergone the first regeneration process) that has not yet been used for purifying organic acid solutions. In addition, regarding PBC in Table 5, the values of PBC for each condition were shown when the PBC under ultrapure water conditions was set to 100%.
[0102]
[0103] As shown in Table 5, when the purification and regeneration of the organic acid solution were repeated a total of 11 times, there was no change in WBC, but a decrease in PBC was observed. Furthermore, if the PBC is below 90% compared to the new resin (under ultrapure water conditions in Table 5), it is still at a level where it can be used for repeated purification; however, from these results, it was found that damage to the resin matrix can be detected early by using PBC rather than WBC as an indicator to measure the deterioration state of the resin. In addition, when the purification and regeneration of the organic acid solution were repeated a total of 11 times, a decrease in PBC was confirmed, but there was no effect on the exchange capacity itself. In other words, it was found that the repeated purification and regeneration of the organic acid solution has a greater effect on the matrix, such as residual cracks in the resin, than on the exchange capacity. The present invention comprises the following configuration.
[0104] [Composition 1]
[0105] A first regeneration process for obtaining a cation exchange resin (B) by contacting a cation exchange resin (A) with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more;
[0106] A purification process for purifying an organic acid solution by contacting the cation exchange resin (B) with an organic acid solution having a metal impurity content of 2 mg / L or less and a concentration of 3 mass% or more; and
[0107] A second regeneration process for obtaining a cation exchange resin (C) by contacting the cation exchange resin (B) after the purification process with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more.
[0108] Method for manufacturing a cation exchange resin having
[0109] [Composition 2]
[0110] A method for manufacturing a cation exchange resin as described in Composition 1, wherein the cation exchange resin (C) obtained in the second regeneration process is reused as a cation exchange resin (B) used in the purification process, and the purification process and the second regeneration process are repeated one or more times.
[0111] [Composition 3]
[0112] A method for manufacturing a cation exchange resin as described in Composition 1 or 2, wherein the above organic acid solution is selected from the group consisting of formic acid, citric acid, oxalic acid, malonic acid, tartaric acid, lactic acid, malic acid, and phosphonic acid.
[0113] [Composition 4]
[0114] A method for manufacturing a cation exchange resin as described in Composition 3, wherein the concentration of the organic acid solution is 3 mass% to 60 mass%, and the total amount of metal impurities of Na (sodium), Mg (magnesium), Ca (calcium), and Fe (iron) in the organic acid solution before purification provided to the purification process is 2 mg / L or less.
[0115] [Composition 5]
[0116] A method for manufacturing a cation exchange resin as described in any one of compositions 1 to 4, wherein the total amount of metal impurities eluted when hydrochloric acid with a concentration of 3 mass% is passed through the cation exchange resin (B) obtained in the first regeneration process at a volume ratio of 25 times is 5 mg / LR or less, and the total amount of metal impurities eluted when hydrochloric acid with a concentration of 3 mass% is passed through the cation exchange resin (C) obtained in the second regeneration process at a volume ratio of 25 times is 5 mg / LR or less.
[0117] [Composition 6]
[0118] A method for manufacturing a cation exchange resin described in any one of compositions 1 to 5, wherein, for a cation exchange resin (C) obtained in the second regeneration process performed arbitrarily and repeatedly, one or more parameters selected from the group consisting of metal impurity content, surface crack condition, and non-sphericity rate are measured at predetermined intervals, and a cation exchange resin (C) that deviates from a predetermined range for each parameter is exchanged with a cation exchange resin not used for purifying an organic acid solution, which is obtained by contacting an inorganic acid solution having a metal impurity content of 1 mg / L or less and a concentration of 5 mass% or more.
[0119] [Composition 7]
[0120] A method for manufacturing a cation exchange resin as described in any one of components 1 to 6, comprising, between the purification process and the second regeneration process, a storage process in which an organic acid solution remaining in the cation exchange resin (B) after the purification process is replaced with water, and the water-replaced cation exchange resin (B) is stored until it is used in the second regeneration process.
[0121] [Composition 8]
[0122] A method for manufacturing a cation exchange resin as described in any one of compositions 1 to 7, wherein the iron (Fe) content in the cation exchange resin (C) obtained in the second regeneration process is less than the iron (Fe) content in the cation exchange resin (B) obtained in the first regeneration process.
[0123] [Composition 9]
[0124] A first regeneration process for obtaining a cation exchange resin (B) by contacting a cation exchange resin (A) with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more; and
[0125] A purification process for purifying an organic acid solution by contacting the cation exchange resin (B) with an organic acid solution having a metal impurity content of 2 mg / L or less and a concentration of 3 mass% or more.
[0126] A method for purifying an organic acid solution comprising,
[0127] A method for purifying an organic acid solution, characterized by reusing the cation exchange resin (B) after the purification process as the cation exchange resin (A) used in the first regeneration process, and repeating the first regeneration process and the purification process one or more times.
Claims
Claim 1 A method for manufacturing a cation exchange resin, comprising: a first regeneration process for obtaining a cation exchange resin (B) by contacting a cation exchange resin (A) with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more; a purification process for purifying an organic acid solution by contacting the cation exchange resin (B) with an organic acid solution having a metal impurity amount of 2 mg / L or less and a concentration of 3 mass% or more; and a second regeneration process for obtaining a cation exchange resin (C) by contacting the cation exchange resin (B) after the purification process with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more. Claim 2 A method for manufacturing a cation exchange resin according to claim 1, wherein the cation exchange resin (C) obtained in the second regeneration process is reused as the cation exchange resin (B) used in the purification process, and the purification process and the second regeneration process are repeated one or more times. Claim 3 A method for manufacturing a cation exchange resin according to claim 1 or 2, wherein the organic acid solution is selected from the group consisting of formic acid, citric acid, oxalic acid, malonic acid, tartaric acid, lactic acid, malic acid, and phosphonic acid. Claim 4 A method for manufacturing a cation exchange resin according to claim 3, wherein the concentration of the organic acid solution is 3 mass% to 60 mass%, and the total amount of metal impurities of Na (sodium), Mg (magnesium), Ca (calcium), and Fe (iron) in the organic acid solution before purification provided to the purification process is 2 mg / L or less. Claim 5 A method for manufacturing a cation exchange resin according to claim 1 or 2, wherein the total amount of metal impurities eluted when hydrochloric acid with a concentration of 3 mass% is passed through the cation exchange resin (B) obtained in the first regeneration process at a volume ratio of 25 times is 5 mg / LR or less, and the total amount of metal impurities eluted when hydrochloric acid with a concentration of 3 mass% is passed through the cation exchange resin (C) obtained in the second regeneration process at a volume ratio of 25 times is 5 mg / LR or less. Claim 6 A method for manufacturing a cation exchange resin according to claim 2, wherein, for a cation exchange resin (C) obtained in the second regeneration process performed repeatedly, one or more parameters selected from the group consisting of metal impurity content, surface crack condition, and non-sphericity rate are measured at predetermined intervals, and a cation exchange resin (C) that deviates from a predetermined range for each parameter is exchanged with a cation exchange resin not used for purifying an organic acid solution, obtained by contacting an inorganic acid solution having a metal impurity content of 1 mg / L or less and a concentration of 5 mass% or more. Claim 7 A method for manufacturing a cation exchange resin according to claim 1 or 2, comprising, between the purification process and the second regeneration process, a storage process in which an organic acid solution remaining in the cation exchange resin (B) after the purification process is replaced with water, and the water-replaced cation exchange resin (B) is stored until it is used in the second regeneration process. Claim 8 A method for manufacturing a cation exchange resin according to claim 1, wherein the iron (Fe) content in the cation exchange resin (C) obtained in the second regeneration process is less than the iron (Fe) content in the cation exchange resin (B) obtained in the first regeneration process. Claim 9 A method for purifying an organic acid solution comprising: a first regeneration process for obtaining a cation exchange resin (B) by contacting a cation exchange resin (A) with an inorganic acid solution having a metal impurity amount of 1 mg / L or less and a concentration of 5 mass% or more; and a purification process for purifying the organic acid solution by contacting the cation exchange resin (B) with an organic acid solution having a metal impurity amount of 2 mg / L or less and a concentration of 3 mass% or more, wherein the cation exchange resin (B) after the purification process is reused as the cation exchange resin (A) used in the first regeneration process, and the first regeneration process and the purification process are repeated one or more times.
Citation Information
Patent Citations
Method for countercurrent regeneration of an ion exchange resin bed
EP1147814B1
Treatment of phosphoric acid extracted solution by ion exchange
JP1982149813A
Regeneration of basic anion-exchange resin
JP1991178340A
Manufacturing method of refined hydrogen peroxide solution
JP2002080209A
Method for producing refined chloride
JP2020001955A